Web-based medicine inventory using decision support system (DDS) approach / Junaini Harshah - Harshah, Junaini (Faculty of Computer and Mathematical Sciences, 2005)
By utilizing the advantages of the World Wide Web (WWW) technology available, which is widely used, inspire the creation of this project A Web-based Medicine Inventory using Decision Support System (DSS) Approach is developed using Apache as the web server, Hypertext Preprocessor (PHP) as the interpreter and Microsoft SQL Server as a database. The main objective of this system is to show how DSS is being used to assist decision making for choosing the best vendor to provide the medicine. The use of DSS is being declared by using fonnula in calculating the rating for vendors. Each vendor which has provided certain medicine will be rated according to certain feature. This is where DSS is being applied in helping phannacist make decision. Beside that this system provides both administrator and pharmacist managing their daily task efficiently. This system provides updating of information and retrieving of data and in an efficient manner and less time consuming.